Multicriteria additive model in generating maps of susceptibility to erosion in rural area - Valladares, Gustavo Souza; Gomes, Andréa da Silva; Torresan, Fabio Enrique; Rodrigues, Cristina Aparecida Gonçalves; Grego, Célia Regina (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the construction of an erosion susceptibility map for a rural area of the municipality of Guararapes, SP, Brazil, using a multicriteria additive model. Digital maps on the themes relief (declivity and length of the slopes), pedology (obtained at the field), land use and land cover of the region, and interpretation of the digital elevation model were used. The digital maps were treated in a geographic information system environment using the additive multicriteria method and were validated by the universal soil loss equation (USLE) model. Five erosion susceptibility classes were generated: low, moderate, high, very high, and extremely high. The risk map obtained by additive multicriteria had good correspondence with the USLE model. The erosion susceptibility map can be used for the agricultural and environmental planning of the rural area of the municipality of Guararapes.
Keywords: geoprocessing; USLE; environmental risk